A Synthesis of Khmer Literature and Identity: A Systematic Review and Meta Analysis - Tithpanha Rim; Sarom Mok; Chhumlong Sum; Som Somuny (Journal of English Language Learning, 2026)
Although the actual duration of human habitation in what is now Cambodia is unknown, clay pot fragments dating back to 4,200 BC have been discovered. The animistic worship practices of the early indigenous people were later combined with Hinduism, which was introduced by Indian traders in the second century. Small kingdoms with Khmer spoken in the villages and Sanskrit at the court were established in Cambodian civilization as a result of the more developed Indian culture. The arrangement eventually led to the rise of a single great king who ruled at Angkor and was revered by local princes. Cambodia now is a different planet. Between 1970 and 1997, a number of civil conflicts and political upheavals tore away the established Buddhist social hierarchy. Within networks of patronage, a new elite of crony capitalists has emerged to replace them. The didactic components of Theravada Buddhist literature have been a crucial governing influence in Cambodia, which has been ruled by elites at least from the time of the Khmer kings in the seventh century. It explores the idea of the ideal woman at the core of the Buddhist social model, and talks about the drastic changes have experienced since the advent of internationalism.